1981
DOI: 10.1111/j.1365-2141.1981.tb02786.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of C3 to Platelets in Vitro by Antiplatelet Antibody from Patients with Immune Thrombocytopenic Purpura

Abstract: Chronic immune thrombocytopenic purpura (ITP) is due to platelet destruction by an IgG antiplatelet antibody. Recent studies by some investigators suggest in vivo fixation of C3 by the antiplatelet antibody in ITP patients; other groups have not confirmed these findings. In the present studies, purified IgG produced in vitro by splenic cells from two patients with ITP resulted in C3 fixation to target platelets. Since cell-bound C3 increases the efficiency of cell destruction in many experimental antibody syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…In vitro studies have given convincing evidence that platelets may fix complement C3 in presence of antiplatelet antibodies [28]. Thus, the rate of elevated PAC3 of 24% in this study is in line with our previous report [ 161.…”
Section: Discussionsupporting
confidence: 93%
“…In vitro studies have given convincing evidence that platelets may fix complement C3 in presence of antiplatelet antibodies [28]. Thus, the rate of elevated PAC3 of 24% in this study is in line with our previous report [ 161.…”
Section: Discussionsupporting
confidence: 93%
“…TNT003 appears to impact CP activation predominantly downstream of C1 binding, and supports the notion that CP activation plays a major role in terminal complement pathway activation in ITP plasma. Indeed, in vitro platelet lysis has been described following normal platelet exposure to autoantibodies from ITP patient sera (McMillan, et al 1981). …”
mentioning
confidence: 99%
“…McMillan and Martin [26] showed that incubation of target platelets with purified IgG synthesized by splenic cells from ITP patients resulted in fixation of C3. Hauch and Rosse [ 131 found 56 % of patients with immune thrombocytopenia to have increased PA-C3, but in no case was PA-C3 increased in the absence of increased PA-IgG.…”
Section: Discussionmentioning
confidence: 99%